Формування медіакомпетентності студентської молоді в єдності навчання і виховання як відповідь на виклики медіатизації - Доброносова, Юлія Дмитрівна (Протидія дезінформації в умовах російської агресії проти України: виклики і перспективи: тези доп. учасників міжн. наук.-практ. конф. (Анн-Арбор - Харків, 12-13 груд. 2023 р.), 2023)
At the current stage of the Russian-Ukrainian war reflection of the mediaeducation is actual because the high level of mediacompetence ensures successful personal resistance to negative media influences. The purpose of the article is reactualization of the unity of education and upbringing in the formation of mediacompetence of student youth. Now the person needs a dynamic mediaexperience for informational resistance in a totally mediatized network society. The spread of new Phygital-presence is a challenge and actual mediaexperience is a response to it. The formation of mediacompetence should become the important task of teaching humanitarian disciplines but it should be combined with an upbringing and the formation of soft skills (critical and creative thinking, teamwork ability).